A comparative analysis of migration systems and migration policies in the European Union and in the Gulf Cooperation Council Countries. (2nd September 2017) - Valenta, Marko
Abstract : Migration systems in the Persian (Arabian) Gulf and Europe are among the largest migration systems in the world and some of the countries in these two systems have emerged as the largest senders and receivers of international migrants. This overview article identifies the major elements of the two systems, and discusses and compares migration trends and policy fields in the systems. It is maintained that the core of the European migration system is the developed wealthy parts of the European Union (EU) while the core of the migration system in the Gulf is the oil-rich monarchies of the Gulf Cooperation Council (GCC). Different historical, economic, political and demographic factors have had an effect on the migration trends. Compared with Europe, the migrations in the Gulf have grown faster and resulted in considerably larger proportions of migrants. Another difference emerges when we compare patterns and scale of internal and external migrations in the two systems. The economic forces are major drivers of labour migrations in the both regions. Yet, stark differences drastically separate the migration realities of the two regions, which partly stem from the decisive difference that separates autocracies in the GCC from European liberal democracies. The GCC countries allow larger immigration of temporary labour migrants, but have clearly less developed and more restrictive practice regarding offering permanent status and citizenship to migrants than the EU's member states. They are also clearly more restrictive regarding refugee/asylum seeker policies, even to refugees from neighbouring Arab countries.